Analisis Minat Mahasiswa Unisma Terhadap Penggunaan E-wallet Dengan Mempertimbangkan Persepsi Kemanfaatan, Persepsi Kemudahan dan Persepsi Kepercayaan - Amani, Muhammad Hilal Ronal; Amin, Moh.; Fakhriyyah, Dewi Diah (e_Jurnal Ilmiah Riset Akuntansi, 2024)
E-wallet is an electronic money transfer system that runs on an application. In this research, the ShopeePay e-wallet was used to see the interests and views of UNISMA students in using e-wallets regarding ease of use, usefulness, and confidence in use. The approach in this research is descriptive quantitative because the focus is on evaluating theory through measuring numerical variables and analyzing statistical data using SPSS. Surveys are used to collect and analyze the data. When using a survey approach, data is collected from specific scientific sources (not artificial), but the process is handled by researchers using tools such as questionnaires and interviews. The results and conclusions show that at the Islamic University of Malang, students' enthusiasm for using the ShopeePay e-wallet is not influenced by their perception of how useful the wallet is. The interest of the Islamic University of Malang students in using the ShopeePay electronic wallet is not influenced by their perception regarding ease of use. Students of the Islamic University of Malang have a good and large influence on their overall interest in using the ShopeePay electronic wallet, this is influenced by their perception of trust.Keywords: Analysis of student interest, perceived benefits, perceived ease, perceived trust, e-wallet.